Answer:
d
Step-by-step explanation:
Given endpoints (x₁, y₁ ) and (x₂, y₂ ) then the midpoint is
( [tex]\frac{x_{1}+x_{2} }{2}[/tex], [tex]\frac{y_{1}+y_{2} }{2}[/tex] )
Here (x₁, y₁ ) = (- 2, - 3) and (x₂, y₂ ) = (1, [tex]\frac{1}{2}[/tex] ), thus
midpoint = ( [tex]\frac{-2+1}{2}[/tex], [tex]\frac{-3+\frac{1}{2} }{2}[/tex] ) = ( [tex]\frac{-1}{2}[/tex], [tex]\frac{-3+\frac{1}{2} }{2}[/tex] ) = ( - [tex]\frac{1}{2}[/tex], [tex]\frac{-\frac{5}{2} }{2}[/tex] ) = ( - [tex]\frac{1}{2}[/tex], - [tex]\frac{5}{4}[/tex] ) → d